Do blacks have a Right to Family Life? an examination of the concept "Ordinary Residence" in Section 10(1)(c) of the Blacks (Urban Areas) Consolidation Act 25 of 1945, as amended - Dixon, Marion L. (Centre for Applied Legal Studies, 1979)
This paper examines the issues arising out of legislation placing restrictions on Blacks' freedom of movement in apartheid South Africa.
Keywords: The Blacks (Urban Areas) Consolidation Act 25 of 1945; Ordinary residence; Freedom of movement; Discrimination; South Africa